THE TRAGEDY OF FELIX FRANKFURTER: FROM CIVIL LIBERTIES AND CIVIL RIGHTS ACTIVIST TO REACTIONARY JUSTICE - Paul Finkelman (Columbia Journal of Race and Law)
This article reconsiders the life and record of Supreme Court Justice Felix Frankfurter. Frankfurter was smart, hardworking, and talented, serving as a great activist lawyer and important law professor in his early career. When nominated to the court, there were high hopes he would follow Holmes and Brandeis in leading a progressive Court that would protect civil liberties and minority rights. However, it was not to be. On the Court Frankfurter became increasingly conservative and ultimately reactionary. In his opinions, he upheld persecution and discrimination of religious and racial minorities, occasionally hindered racial justice and civil liberties efforts, and opposed due process in criminal trials and fairness in elections. Arrogant and dismissive, he constantly fought with his brethren, alienating almost all of them. In the end Frankfurter was far too often on the wrong side of history, liberty and the law, and even legal ethics. The tragedy of Frankfurter is that he abandoned the constitutional rights and protections that he supported from his graduation from law school until he donned his robes. He could have been a great justice. Sadly, he was not.